Antecedents and consequences of professional competence of school administrators with emphasis on environmental sustainability and sustainable development - mohamadreza rasouli; ghafar tari; hossein Baghaei (مدیریت و چشم انداز آموزش)
Abstract The aim of the present research is to investigate the antecedents and consequences of professional competence of school managers with an emphasis on environmental sustainability and sustainable development. The research method is applicable in terms of purpose, and mixed (qualitative-quantitative) in terms of implementation. The statistical population of this research in the qualitative section included experts and professors in the field of education in Tehran, who were sampled purposefully; and in the quantitative section, school managers in Tehran who were selected through random-stratified sampling for the validation of the research model. In the qualitative part of the research, data and information were collected through interviews with experts and professors in the field of education, and then the model of professional competence of school managers as a key driver of sustainable development was validated based on a questionnaire. MAXQDA 18 and PLS-Smart 3 software were used for data analysis. The research findings indicated that the model of professional competence of managers includes competence-building skills, managerial competencies, ethical competencies and professional behavior, manager development, social indicators of managers, establishment of work groups for performance improvement and green competence, attitude competencies, knowledge competencies, educational competencies, commercialization competencies of knowledge, skills and technology, work ethic, consumption pattern improvement, participation in development, and moving towards national empowerment, leading to the realization of work ethic results, consumption pattern improvement, participation in development, movement towards national empowerment, diversity management, and enhancing the relationship between humans and nature. Extended abstract Introduction Performance sustainability is a relatively new concept defined as a process that focuses on all five dimensions of sustainability performance (economic, governance, social, ethical, and environmental) (Atstsaury et al, 2024). Serious action has not been taken to address environmental pollution, especially in the field of human resource development and professional development (Hustler & McIntyre, 2024). With growing public concerns about the long-term consequences of environmental issues and climate change, and its negative impact on the growth and development of societies, particularly in less developed countries, proactive and innovative measures have been taken to embrace environmental responsibilities and professional competencies. Previous research findings in the area of the current research topic indicate that the perspectives of past researchers on the subject of professional development of managers as a key factor in sustainable development have been different. Some have approached the issue of professional development with an organizational perspective and organizational requirements, while others have looked at it from an individual and personal perspective, seeking the missing link in individual requirements such as a sense of responsibility and environmental attitudes. And as it was mentioned before, some researchers consider organizational requirements and organizational mandates sufficient to change employee behavior. However, another group of researchers has examined both individual and organizational factors but have not provided a model and have not focused on future trends and factors that create sustainable development. Unfortunately, in their research findings, they have also not considered the characteristics of the education sector. Therefore, the aim of this research is to explore the antecedents and consequences of professional competence of school managers with an emphasis on environmental sustainability and sustainable development. Theoretical Framework Professional competencies include skills, knowledge, and attitudes. This means that it is not easy to say that one factor is part of knowledge, skills, or attitudes. Some other experts have also identified other elements of professional competencies; factors such as motivation, self-awareness, personal factors, values, beliefs, and other factors that play a significant role in job success. In the past decade, various models and frameworks have been proposed for measuring competencies, and these models often differ in the information they gather. Some models emphasize generic abilities and qualitative characteristics of individuals, while another group of models focuses on specific technical skills for the job. Some models have attempted to present in a comprehensive approach, by considering job roles, job behaviors, and knowledge-skill-ability, present a combination of individual competencies and job competency areas. Today, there are various models and frameworks for competencies, but it can be said that most of them are somewhat based on these factors (Sancar et al, 2021):